Physiological Maturity of Tropical Forest Seeds: A Boon to Improved Harvest and Storage Practice of Recalcitrant Seeds? - Vidya, P. R.; Jose, P. A. (International Journal of Economic Plants, 2023)
The fruit harvest at physiological maturity of seeds is a globally accepted practice. This method has been traditionally practiced in horticultural crops where quality seeds and vigorous seedlings are ensured for cultivation of the species. The assessment of seed physiological maturity in the harvest of forest fruits and seeds are seldom practiced as seed physiological and biochemical studies in tropical seeds is little attempted. Since recalcitrant seed behavior among forest species is increasing, maintenance of seed viability and longevity ex situ becoming a challenging task in the forestry sector. Further, seed loss through fruit predation and pest infestation are other handicaps to these species. An improved technology for harvesting, storage and longevity of recalcitrant seeds will be a breakthrough for the germplasm conservation, management and utilization of forest genetic resources. Identification of biochemical factors at physiological maturity of seeds in conjunction with fruit morphological characters considered as optimum harvest practice for recalcitrant forest fruits and seeds. The practice could extend shelf life of recalcitrant seeds and bypass seed loss prior to the conventional harvest practices. This review outlines the research works carried out in seed physiological maturity of crops and its broad scope among recalcitrant forest seeds for long term germplasm storage.